Larvicidal Activity of Zingiber purpureum Roscoe Essential Oil from East Kalimantan in Preventing Dengue Hemorrhagic Fever: Efficacy Test of Zingiber purpureum Roscoe Essential Oil as a Natural Larvicide - Syahdumawarta, Lirana Imute; Toruan, Vera Madonna Lumban; Paramita, Swandari; Zubaidah, Mona (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Temephos is extensively employed currently to eliminate Aedes aegypti mosquito larvae, thus preventing the spread of dengue fever. Raising the level of temephos application can lead to health issues for individuals and long-term detrimental impacts on the environment. This research aims to demonstrate that Z. purpureum Rosc. essential oil effective in eliminating more than 70% of Aedes aegypti mosquito larvae. Z. purpureum Rosc.essential oil was diluted with Tween 80 to achieve various concentrations, namely 12.5 μg/mL, 25 μg/mL, 50 μg/mL, and 100 μg/mL. A positive control was established using temephos at a concentration of 0.012 mg/L, while a negative control was prepared using clean water. The larvae were subjected to these treatments for a duration of 48 hours, with three repetitions conducted. The data were analyzed using the Kruskal Wallis Test that shows a significant difference between treatment groups, with a p value <0.05. A concentration of 12.5 μg/mL of Z. purpureum Rosc. essential oil was found to effectively eliminate 76.67% of Aedes aegypti mosquito larvae. A concentration of 25 μg/mL of Z. purpureum Rosc. essential oil was found to effectively eliminate 86.67% of Aedes aegypti mosquito larvae. A concentration of 50 μg/mL of Z. purpureum Rosc. essential oil was found to effectively eliminate 96.67% of Aedes aegypti mosquito larvae. A concentration of 100 μg/mL of Z. purpureum Rosc. essential oil was found to effectively eliminate 100% of Aedes aegypti mosquito larvae. The overall findings show that more than 70% of Aedes aegypti mosquito larvae are effectively killed by Z. purpureum Rosc. essential oil at a concentration of 12.5 μg/mL.